Metalinguagens e plurissignificação em Guimarães Rosa: uma leitura de Tutaméia - SILVA, Narjara Mendes (2017)
The present research invests itself in the responsibility of analyzing, from thematic groups, some short stories of Tutaméia (1967), the last book published by João Guimarães Rosa in which we find a magisterial work of language fictionalization in which each word and act of the characters carry An over meaning, plurissignific. Although some works by the author, such as Grande sertão: veredas, possess a considerable critical fortune, the same can not be said of Tutaméia, who continues to demand reading and reflection. Before these premises, we selected the following stories: Os três homens e o boi, Lá, nas campinas, João Porém, o criador de perus, Desenredo, (first part), Azo de almirante and Curtamão, (second part). For this work, we approve of some theories: Semiotics, as an important observer of language and existentialist phenomenology, through the focus on perception and experience in understanding the phenomena of human existence. Considering the literary text as a sign phenomenon, we use the assumptions of these theories that seek, respectively, to interpret the process of production of signs and the functions of human language beyond its relations with thought. In addition, we seek the contributions of authors such as Haroldo de Campos, Vera Novis, Paulo Rónai, Antonio Cândido, Maria Célia Leonel, Benedito Nunes who have already embarked on the universe of the narratives of Guimarães Rosa, among others. Therefore, the fictional space of Rosian tales allows us to think of the creative force of language in which human drama is represented artistically through the dramas of its characters in a movement where the imaginary and the universal are confused.